Solar Physics From Unconventional Viewpoints - Gibson, Sarah E.; Vourlidas, Angelos; Hassler, Donald M.; Rachmeler, Laurel A.; Thompson, Michael J.; Newmark, Jeffrey; Velli, Marco; Title, Alan; McIntosh, Scott W. (Frontiers in Astronomy and Space Sciences, 2018)
We explore new opportunities for solar physics that could be realized by future missions providing sustained observations from vantage points away from the Sun-Earth line. These include observations from the far side of the Sun, at high latitudes including over the solar poles, or from near-quadrature angles relative to the Earth (e.g., the Sun-Earth L4 and L5 Lagrangian points). Such observations fill known holes in our scientific understanding of the three-dimensional, time-evolving Sun and heliosphere, and have the potential to open new frontiers through discoveries enabled by novel viewpoints.